2021
DOI: 10.4252/wjsc.v13.i5.342
|View full text |Cite
|
Sign up to set email alerts
|

Multidifferentiation potential of dental-derived stem cells

Abstract: Tooth-related diseases and tooth loss are widespread and are a major public health issue. The loss of teeth can affect chewing, speech, appearance and even psychology. Therefore, the science of tooth regeneration has emerged, and attention has focused on tooth regeneration based on the principles of tooth development and stem cells combined with tissue engineering technology. As undifferentiated stem cells in normal tooth tissues, dental mesenchymal stem cells (DMSCs), which are a desirable source of autologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 217 publications
0
9
0
Order By: Relevance
“…It was reported that BIO promoted the proliferation of human periodontal ligament stem cells (PDLSCs) [ 40 ], rat marrow-derived mesenchymal stem cells [ 41 ], and rat cardiomyocytes [ 42 ]. In contrast, other studies demonstrated that BIO decreased cell proliferation in stem cells isolated from human exfoliated deciduous teeth [ 40 ], hDPSCs [ 43 ], ovarian cancer cells [ 44 ], a mouse myoblast cell line [ 45 ], canine BMSCs [ 46 ], and canine melanoma cell lines [ 47 ]. Similarly, the effect of Wnt on cell migration remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BIO promoted the proliferation of human periodontal ligament stem cells (PDLSCs) [ 40 ], rat marrow-derived mesenchymal stem cells [ 41 ], and rat cardiomyocytes [ 42 ]. In contrast, other studies demonstrated that BIO decreased cell proliferation in stem cells isolated from human exfoliated deciduous teeth [ 40 ], hDPSCs [ 43 ], ovarian cancer cells [ 44 ], a mouse myoblast cell line [ 45 ], canine BMSCs [ 46 ], and canine melanoma cell lines [ 47 ]. Similarly, the effect of Wnt on cell migration remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systematic reviews have now investigated the use of exosomes for the treatment of various dental tissues. [1050][1051][1052][1053][1054][1055][1056][1057][1058][1059][1060] In fact, part 3 of this 3-part series is dedicated entirely to the use of exosomes in dentistry. In that systematic review, a total of 944 articles were identified using exosomes in the dental field for either their regenerative/therapeutic potential or for diagnostic purposes derived from salivary exosomes.…”
Section: Dental Regenerationmentioning
confidence: 99%
“…Regenerative medicine using stem cells is currently attracting increased attention [9,10], but there are many challenges in the clinical applications of totipotent and pluripotent stem cells [11,12,13]. DPSCs are attracting special attention for their potential applications in regenerative medicine due to their easy accessibility and broad capacity for differentiation [14][15][16][17]. Currently, several treatment modalities exist that take advantage of the ability of DPSCs to differentiate into odontoblasts, including direct pulp capping, pulpotomy and indirect pulp capping [18,19,20].…”
Section: Introductionmentioning
confidence: 99%